IMPLEMENTASI PEMBELAJARAN BERBASIS PROJECT BASED LEARNING DALAM UPAYA MENINGKATKAN NILAI NILAI KARAKTER DAN KEMANDIRI-AN BERBAHASA INDONESIA DI SMP NEGERI 1 KLATEN TAHUN PELAJARAN 2025/2026 - Puji Wahyu Harjanti; Triyono; Dwi Bambang Putut Setiyadi; Hersulastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the implementation of project-based learning (PjBL) in improving: (1) students’ learning activities, (2) character values, and (3) learning independence in Indonesian language among eighth-grade students of SMP Negeri 1 Klaten in the 2025/2026 academic year. The research used a Classroom Action Research (CAR) method conducted in two cycles, consisting of planning, action, observation, and reflection stages. The results indicate that PjBL effectively enhanced students’ learning activity and creativity, with an improvement from 77.77% (good) in cycle I to 93.51% (very good) in cycle II. Students also showed positive growth in character values such as responsibility, cooperation, and honesty. Furthermore, their learning independence in Indonesian literacy improved as they engaged in project creation. Thus, project-based learning proved effective in enhancing students’ learning activity, character values, and learning independence.